Execution of the Public State Receivables under Art. 162, Par. 6 of the Tax and Social Security Procedure Code - Simeonova, Ginka (Yearbook of the Law Department, 2019)
The public state receivables, regulated in art. 162, par. 6 Tax and Social Security Procedure Code have a number of specifics, caused by the nature and type of the offenses from which they arise, the bodies, which establish them, the acts, which make them liquid and due and the order for their execution. The article examines precisely the procedure for execution of public state receivables, regulated in the abovementioned provision.